Relationship between COVID-19 and iron deficiency anemia in pregnant women - Sergey P. Sinchikhin; Lusine V. Stepanyan; Lyubov M. Atueva; Onsi Nasri; Ekaterina S. Sinchikhina (IP Berlin A.V., 2021)
Huge resources of the health system and economies of all countries of the world are devoted to combating the COVID-19 pandemic (Coronavirus disease 2019). It is important to formulate effective measures to prevent the spread of a new coronavirus infection and the development of its postcoid complications. For this, it is necessary to study in depth not only the etiopathogenesis, clinical manifestations of the disease, but also to assess the influence of another pathology on the course of the development of the disease. Particular attention should be paid to pregnant patients with COVID-19. To clarify the relationship between COVID-19 and iron deficiency anemia. The information material includes data from scientific articles available in Pubmed and Internet resources on this topic, as well as data from our own observations. Timely diagnosis and treatment of iron deficiency anemia in pregnant women helps not only to prevent the development of obstetric and perinatal complications, but also to prevent the development of a severe course of COVID-19.